SYNTHESIS AND CHARACTERIZATION OF A GRAPHENE OXIDE-CHITOSAN NANOCOMPOSITE FOR THE ADSORPTION OF HEAVY METALS FROM INDUSTRIAL WASTEWATER - Kim Minho; Wang Jun; Sebastian Koch (Yayasan Adra Karima Hubbi, 2025)
The contamination of industrial wastewater with heavy metals such as lead (Pb), cadmium (Cd), and chromium (Cr) poses a significant environmental threat, requiring effective removal methods. Traditional water treatment techniques often suffer from inefficiency and environmental harm. This study aims to synthesize and characterize a graphene oxide-chitosan nanocomposite for the efficient adsorption of heavy metals from industrial wastewater. Graphene oxide (GO) was combined with chitosan to form the nanocomposite, which was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET) surface area analysis. The adsorption capacity was evaluated through batch experiments using simulated industrial wastewater, and the effects of pH, contact time, and metal concentration on adsorption were examined. The results showed that the nanocomposite demonstrated excellent adsorption efficiency, with the highest removal rate observed for Pb, followed by Cd and Cr. The adsorption capacity was significantly influenced by pH, with optimal performance at pH 5. The nanocomposite exhibited high metal removal efficiency and stability, indicating its potential as an eco-friendly solution for wastewater treatment. This study highlights the potential of graphene oxide-chitosan nanocomposites as effective adsorbents for heavy metal removal, offering a sustainable alternative to traditional treatment methods.